FPGA Based Symmetrical Multi Level Inverter with Reduced Gate Driver Circuits - G. Durga Prasad; V Jegathesan (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
Multilevel converters tender advantages in terms of the output waveform quality due to the increased number of levels used in the output voltage modulation and have been widely accepted for high-power high-voltage applications.  This paper introduces topology in multilevel dc link inverter (MLDCLI), which can significantly reduce the switch count and improve the performance. The preferred topology provides a dc voltage with the shape of a staircase approximating the rectified shape of a commanded sinusoidal wave, to the bridge inverter, which in turn gives the required alternating waveform. This topology requires fewer components compared to traditional Multi level Inverters (MLI).Therefore, the overall cost and complexity are significantly reduced particularly for higher output voltage levels. Finally, Matlab/Simulink and XILINX are used as a simulation and compiler architecture of control circuit embedded in FPGA. Simulation and experimental results for fifteen-level inverter are presented for validation.